Feminities, masculinities, sexualities: Freud and beyond - Chodorow, Nancy J. (The University Press of Kentucky, 1994)
La psychanalyse peut-elle aller au-delà d'une vision monolithique du genre et de la sexualité normale pour aborder les questions de diversité et de variabilité dans le développement du genre et l'identité de genre ? Ses praticiens et théoriciens peuvent-ils rendre des comptes rendus non pathologisants de la variation de l'orientation sexuelle ? S'appuyant sur une lecture attentive des textes psychanalytiques commençant par Freud et sur sa propre expérience clinique, Chodorow [soutient] que la psychanalyse doit encore démêler la domination masculine de l'hétérosexualité. Elle démontre également le manque de compréhension psychanalytique de l'hétérosexualité et la polarisation problématique des sexualités normales et anormales. Chodorow soutient que la psychanalyse doit prêter attention à la spécificité individuelle et au cadre personnel, culturel et social
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; domination masculine; fem1000; genre; hétérosexisme; hétérosexualité; identités LGBTQIA2+; premier cycle; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

The Heterosexual Imaginary: Feminist Sociology and Theories of Gender - Ingraham, Chrys (Sociological Theory, 1994)
This essay argues that the material conditions of capitalist patriarchal societies are more integrally linked to institutionalized heterosexuality than they are to gender. Building on the critical strategies of early feminist sociology through the articulation of a materialist feminist theoretical framework, the author provides a critique of contemporary sex-gender theory. She argues that the heterosexual imaginary in feminist sociological theories of gender conceals the operation of heterosexuality in structuring gender and closes off any critical analysis of heterosexuality as an organizing institution.... every sociological concept and thesis, as well as the overall patterning of these concepts and theses, is potentially open for reconsideration... With the emergence of feminist sociological theory, the critical emphases in sociology are strengthened by an insistence that sociological work be critical and change-oriented... in an intensely reflexive way towards sociology itself (Lengermann and Niebrugge-Brantley 1990:318). We must produce a political transformation of the key concepts, that is of the concepts which are strategic for us (Wittig 1992:30).
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; féminisme matérialiste; histoire et politique; hétérosexisme; hétérosexualité; patriarcat; premier cycle; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Sodomites, invertis, homosexuels: perspectives historiques - Mendès-Leite, Rommel (Cahiers Gai-Kitsch-Camp, 1994)
Section: 193 pages : illustrations ; 21 cm
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

The Politics of Inside/Out: Queer Theory, Poststructuralism, and a Sociological Approach to Sexuality - Namaste, Ki (Sociological Theory, 1994)
This paper outlines the main tenets of poststructuralism and considers how they are applied by practitioners of queer theory. Drawing on both Michel Foucault and Jacques Derrida, queer theory explores the ways in which homosexual subjectivity is at once produced and excluded within culture, both inside and outside its borders. This approach is contrasted with more sociological studies of sexuality (labeling theory, social constructionism). Whereas queer theory investigates the relations between heterosexuality and homosexuality, sociologists tend to examine homosexual identities and communities, paradoxically ignoring the social construction of heterosexuality. Poststructuralism can inform a sociological approach to sexuality by emphasizing the generative character of all sexual identities. A sociological study of sexuality which is informed by poststructuralism would examine the exclusions implicit in a heterosexual/homosexual opposition. In this process, bisexual and transgender identities can become viable cultural possibilities, and a broad-based political coalition established. Whereas mainstream sociology focuses on the ways in which homosexuals are outside social norms, and whereas queer theory exploits the ways in which this outside is already inside, this perspective suggests that a critical sexual politics seeks to move beyond an inside/outside model.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; méthodologie; post-structuralisme; premier cycle; queer; sciences humaines; sexualité; soc2014; sociologie; thématiques